Analysis of Pump Requirements for Mine Dewatering Sump at Kerinci PT Cipta Kridatama Jobsite PT Kuansing Inti Makmur - Nauli, Fitri; Irfan, Aulia; Yanti, Syari Rahma; Alghifari, Arif; Deny, Andri Van (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2024)
Sump Kerinci PT Cipta Kridatama, the jobsite of PT Kuansing Inti Makmur, covers an area with coal reserves at an elevation of 26 meters. However, due to the high intensity of rain, the elevation of the sump increased to 38 meters, hampering mining activities. This study aims to design an efficient dewatering solution through the calculation of planned rainfall, runoff water discharge, and pump requirements, with a specific approach to the design of the open-pit mine drainage system at the research site. The research method involves analyzing historical rainfall data over the past eight years to calculate planned rainfall, rainfall intensity, and runoff water discharge using the Gumbel hydrological method. Pump requirements are calculated based on the technical specifications of the centrifugal pump and the topographical characteristics of the site. From the results of the analysis, it takes 24 pumps to dry the sump in one day, but this approach is not economical. Alternatively, the use of 3 pump units operating for 63 days is proposed as the optimal solution to reduce operational costs and meet the need for dewatering for two months. Sump Kerinci PT Cipta Kridatama, jobsite PT Kuansing Inti Makmur, mencakup area dengan cadangan batubara pada elevasi 26 meter. Namun, akibat intensitas hujan yang tinggi, elevasi sump meningkat hingga 38 meter, menghambat aktivitas tambang. Penelitian ini bertujuan untuk merancang solusi dewatering yang efisien melalui perhitungan curah hujan rencana, debit air limpasan, dan kebutuhan pompa, dengan pendekatan spesifik terhadap desain sistem penyaliran tambang terbuka di lokasi penelitian. Metode penelitian melibatkan analisis data historis curah hujan selama delapan tahun terakhir untuk menghitung curah hujan rencana, intensitas hujan, dan debit air limpasan menggunakan metode hidrologi Gumbel. Kebutuhan pompa dihitung berdasarkan spesifikasi teknis pompa sentrifugal dan karakteristik topografi lokasi. Dari hasil analisis, dibutuhkan 24 unit pompa untuk mengeringkan sump dalam satu hari, namun pendekatan ini tidak ekonomis. Sebagai alternatif, penggunaan 3 unit pompa yang beroperasi selama 63 hari diusulkan sebagai solusi optimal untuk menekan biaya operasional dan memenuhi kebutuhan dewatering selama dua bulan.